M+6=-2m+6

Simple and best practice solution for M+6=-2m+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for M+6=-2m+6 equation:


Simplifying
M + 6 = -2m + 6

Reorder the terms:
6 + M = -2m + 6

Reorder the terms:
6 + M = 6 + -2m

Add '-6' to each side of the equation.
6 + -6 + M = 6 + -6 + -2m

Combine like terms: 6 + -6 = 0
0 + M = 6 + -6 + -2m
M = 6 + -6 + -2m

Combine like terms: 6 + -6 = 0
M = 0 + -2m
M = -2m

Solving
M = -2m

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Simplifying
M = -2m

See similar equations:

| (7x+4)-(24x-15)=180 | | 0.2(z+15)=3 | | 0.4x-1.2=0.15x+1.8 | | n(n-1)(n-2)(n-3)-84=0 | | y^4+26y^3+169y^2-900=0 | | h=-5 | | 15+8x=45+6x | | 11-6n=29 | | (3k+5)(-k)= | | 3(4x-4)+52=6x+4 | | 5x+1=6x+17 | | 3x+52=80 | | 2015=101b+19a | | 3c-7=-3+1 | | 47=47-8(5-1w) | | 2y=3y+19 | | 4x-2=2x+x+4 | | 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 | | 8-w=8 | | h=81.688+2.392*50.1 | | 3(6+5y)= |

Equations solver categories